Short-Term Intensive Therapy in Newly Diagnosed Type 2 Diabetes Partially Restores Both Insulin Sensitivity and β-Cell Function in Subjects With Long-Term Remission - Hu, Yun (American Diabetes Association, 2011)
OBJECTIVE: To examine the effect of intensive glycemic control therapy (IT) on insulin sensitivity and β-cell function in newly diagnosed type 2 diabetic patients compared with subjects with normal glucose tolerance (NGT) and those with impaired glucose tolerance (IGT). RESEARCH DESIGN AND METHODS: Forty-eight newly diagnosed type 2 diabetic patients were randomly assigned to IT for 2 weeks and followed up for 1 year. Intravenous glucose tolerance tests were conducted in NGT, IGT, and diabetic subjects. Blood glucose and insulin were measured before and after IT and at the 1-year follow-up. RESULTS: IT lowered the homeostasis model assessment (HOMA) for insulin resistance (IR) significantly, from 3.12 ± 1.4 (mean ± SD) to 1.72 ± 0.8, a level comparable to the IGT (1.96 ± 1.1) and NGT (1.37 ± 0.6) subjects in the remission group; however, no HOMA-IR improvement was observed in nonremission subjects. HOMA-β in the remission group was improved (mean, interquartile range) from 18.4 (8.3–28.5) to 44.6 (32.1–69.1) and acute insulin response of insulin (AIRins) from 1.50 ± 0.22 to 1.83 ± 0.19 μIU/mL after IT, but was still significantly lower than those in NGT individuals (HOMA-β: 86.4 [56.7–185.2], P < 0.01; AIRins: 2.54 ± 0.39 μIU/mL, P < 0.01). After IT and at 1 year, the hyperbolic relationship between HOMA-β and HOMA sensitivity of remission subjects shifted close to that of IGT subjects. CONCLUSIONS: IT in newly diagnosed type 2 diabetes not only partially restored β-cell function but also greatly restored insulin sensitivity. Compared with IGT and NGT subjects, β-cell function was less restored than insulin sensitivity after IT in the remission subjects.